Studies on the Optical Properties and Surface Morphology of Cobalt Phthalocyanine Thin Films - Benny Joseph; C. S. Menon (E-Journal of Chemistry)
Thin films of Cobalt Phthalocyanine (CoPc) are fabricated at a base pressure of 10-5 m.bar using Hind-Hivac thermal evaporation plant. The films are deposited on to glass substrates at various temperatures 318, 363, 408 and 458K. The optical absorption spectra of these thin films are measured. The present studies reveal that the optical band gap energies of CoPc thin films are almost same on substrate temperature variation. The structure and surface morphology of the films deposited on glass substrates of temperatures 303, 363 and 458K are studied using X-ray diffractograms and Scanning Electron Micrographs (SEM), which show that there is a change in the crystallinity and surface morphology due to change in the substrate temperatures. Full width at half maximum (FWHM) intensity of the diffraction peaks is also found reduced with increasing substrate temperatures. Scanning electron micrographs show that these crystals are needle like, which are interconnected at high substrate temperatures. The optical band gap energy is almost same on substrate temperature variation. Trap energy levels are also observed for these films.